1999
DOI: 10.1046/j.1365-2435.1999.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Strategic sperm allocation in the Small White butterfly Pieris rapae (Lepidoptera: Pieridae)

Abstract: Summary 1.In species where females mate multiply, it is important for males to recuperate quickly in order to maximize their fertilization success. Butterflies produce a spermatophore at mating containing accessory secretions and sperm of two types: a large number of nonfertile 'apyrene' sperm and fewer fertile 'eupyrene' sperm. Many butterfly species eclose with most nutrients for reproduction already present. Males must therefore decide how to allocate resources to the various spermatophore components at any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 59 publications
(72 reference statements)
3
33
0
Order By: Relevance
“…2). A positive association between a male size and spermatophore mass that had been reportedly found in butterflies and other insects (Bissoondath and Wiklund, 1996;Karlsson, 1998;Wedell and Cook, 1999;Wiklund and Kaitala, 1995) confirms our findings. Further, this finding corroborates previous finding that spermatophore mass and fertile sperm numbers increased with male size, while non fertile sperm numbers were unrelated to male size (Fischer et al, 2009;Lewis and Wedell, 2007).…”
Section: Male Size and Sperm Numbersupporting
confidence: 92%
See 2 more Smart Citations
“…2). A positive association between a male size and spermatophore mass that had been reportedly found in butterflies and other insects (Bissoondath and Wiklund, 1996;Karlsson, 1998;Wedell and Cook, 1999;Wiklund and Kaitala, 1995) confirms our findings. Further, this finding corroborates previous finding that spermatophore mass and fertile sperm numbers increased with male size, while non fertile sperm numbers were unrelated to male size (Fischer et al, 2009;Lewis and Wedell, 2007).…”
Section: Male Size and Sperm Numbersupporting
confidence: 92%
“…Earlier reports also revealed that male provided larger females with ejaculates frequently contain more sperm that have increased fecundity in many insects (Engqvist and Suer, 2003;Gage, 1998;Gage and Barnard, 1996;Wedell and Cook, 1999). That at least some male Lepidoptera seem capable of assessing female quality and reproductive potential, and adjust their ejaculate accordingly.…”
Section: Lifetime Fecunditymentioning
confidence: 91%
See 1 more Smart Citation
“…The contribution from the males can be quite substantial, and in Pieris napi multiply mated females attain almost twice the fecundity of females that have mated only once. Hence, females often forage for matings (Kaitala & Wiklund 1994), and in the light of the bene¢ts accrued monandry as a female strategy can be more problematic to explain than polyandry (Arnqvist & Nilsson 2000;Wedell et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unknown whether there is a positive relationship between copulation duration and ejaculate transfer in soldier flies. Males have been shown to adjust ejaculate size in response to SC in several species (Gage 1991;Wedell and Cook 1999;Engqvist 2007;Ramm et al 2009), and there are numerous examples that show that larger ejaculates result in higher fertilization success (Simmons 1987;Simmons et al 1996;Arnqvist and Danielsson 1999).…”
Section: Discussionmentioning
confidence: 99%